2018
DOI: 10.1093/cercor/bhy312
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Inner and Outer Fiber Layers in the Developing Cerebral Cortex of Gyrencephalic Ferrets

Abstract: Changes in the cerebral cortex of mammals during evolution have been of great interest. Ferrets, monkeys, and humans have more developed cerebral cortices compared with mice. Although the features of progenitors in the developing cortices of these animals have been intensively investigated, those of the fiber layers are still largely elusive. By taking the advantage of our in utero electroporation technique for ferrets, here we systematically investigated the cellular origins and projection patterns of axonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…In qualitative terms, the ferret shares some neurodevelopmental features with humans that are completely lacking in the mouse. Those include, but are not limited to, the expansion of the SVZ and distinction of the oSVZ ( Reillo and Borrell, 2012 ), abundance of BPs and particularly proliferative bRG ( Fietz et al, 2010 ; Reillo et al, 2011 ; Kalebic et al, 2019 ), morphological heterogeneity of bRG ( Kalebic et al, 2019 ), tangential dispersion of migrating neurons ( Gertz and Kriegstein, 2015 ), presence of both inner and outer fiber layers ( Saito et al, 2018 ), and neocortical folding ( De Juan Romero et al, 2015 ; Figure 1 ). Albeit present in both the human and ferret, most of the features mentioned are quantitatively reduced in the ferret.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In qualitative terms, the ferret shares some neurodevelopmental features with humans that are completely lacking in the mouse. Those include, but are not limited to, the expansion of the SVZ and distinction of the oSVZ ( Reillo and Borrell, 2012 ), abundance of BPs and particularly proliferative bRG ( Fietz et al, 2010 ; Reillo et al, 2011 ; Kalebic et al, 2019 ), morphological heterogeneity of bRG ( Kalebic et al, 2019 ), tangential dispersion of migrating neurons ( Gertz and Kriegstein, 2015 ), presence of both inner and outer fiber layers ( Saito et al, 2018 ), and neocortical folding ( De Juan Romero et al, 2015 ; Figure 1 ). Albeit present in both the human and ferret, most of the features mentioned are quantitatively reduced in the ferret.…”
Section: Discussionmentioning
confidence: 99%
“…This method was first applied to ferrets by Kawasaki and colleagues and it consists of an intraventricular injection of genetic material and subsequent electroporation to permit the entry of delivered molecules to the neuroepithelium ( Kawasaki et al, 2012 , 2013 ; Kalebic et al, 2020 ; Figures 3B,E ). In utero electroporation has been widely used in ferrets to study the cell biology of neural progenitors ( Kalebic et al, 2019 ; Kostic et al, 2019 ; Güven et al, 2020 ; Matsumoto et al, 2020 ; Xing et al, 2020 ), histological features of ferrets neurodevelopment ( Martinez-Martinez et al, 2016 ; Saito et al, 2018 ), and cortical folding ( Toda et al, 2016 ; Matsumoto et al, 2017b ; Shinmyo et al, 2017 ). Of importance for translational research, in utero electroporation is increasingly being used to express human-specific genes ( Kalebic et al, 2018 ) and to model human neurodevelopmental pathologies in ferrets ( Masuda et al, 2015 ; Matsumoto et al, 2017a ).…”
Section: Techniques For Functional Studies In Ferretsmentioning
confidence: 99%
“…Recent studies have shown that both rodents and ferrets share similar fiber layer structures in the cerebral cortex with primates: the outer fiber layer of intracortical projections and the inner fiber layer of intercortical and subcortical projections ( Kawasaki et al. 2013 ; Saito et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…6A) 29 . Eventual organization along the full perimeter of the ventricle has been reported in slightly later stages of development 39,40 . This organization of fibers around the ventricle, which occurred prior to folding, is consistent with well-established axon tracts, such as the corpus callosum and optic radiations, that wrap around the lateral ventricles in both gyrencephalic and lissencephalic species.…”
Section: Axon Organization As a Consequence Rather Than A Cause Of mentioning
confidence: 93%